Food waste disposal and utilization in the United States: A spatial cost benefit analysis. (10th September 2021) - Badgett, Alex; Milbrandt, Anelia
Abstract: Food waste is generated from residential, commercial, institutional, and industrial sources, and is conventionally disposed of in landfills. To nurture the development of a circular economy for food waste, its valorization by technologies that create fuels, power, or products is being investigated. These technologies offer the potential to dispose food waste while generating sustainable resources. While some literature exists on the economics of food waste utilization options, no existing study simultaneously characterizes different facility scales and locations across many food waste pathways. This study develops a series of cost-benefit models that depict the economic favorability of several food waste management pathways by state: landfilling, composting, anaerobic digestion, incineration, and biofuels production via hydrothermal liquefaction. Economic favorability primarily depends on the local tipping (gate) fee charged by the facility; however, additional revenue streams realized from the sale of biofuels, biopower, or bioproducts can reduce this dependence. Local market prices for biofuels, biopower, or bioproducts generated from food waste determine the profitability of technologies that generate these products. The magnitude of these revenue streams depends on local market factors and the economies of scale leveraged for large facilities. Significant spatial variability in these results exists across the United States, driven by the differences in tipping fees, O&M costs (e.g., labor rates), and product market prices. This study supports decision-making by industry, state, and local governments, as well as furthering research in the area of sustainable utilization of food waste. Graphical abstract: Image 1 Highlights: First study to analyze spatial variability of food waste pathway economics. Economies of scale are evident for all food waste pathways. Profitability of food waste pathways depends on local market factors. Bioenergy from food waste can generate significant revenue streams. Bioenergy economics are sensitive to energy potential and waste degradation rates.